BENTUK DAN CIRI KHAS MASJID PATHOK NEGORO DONGKELAN - Amini, Anggun Rizka; Permana, R. Cecep (UI Scholars Hub, 2026)
Masjid Pathok Negoro Dongkelan is one of the kagungan dalem mosques belonging to the Yogyakarta Sultanate, constructed as part of the spiritual and administrative structure of the Kraton’s territory. This study examines the architectural form and distinctive characteristics of Masjid Pathok Negoro Dongkelan using a comparative method with other Pathok Negoro mosques as well as the Great Mosque of Kauman (Masjid Gedhe Kauman). The findings indicate that Masjid Dongkelan possesses unique architectural features, including a fully enclosed veranda, a covered pulpit with a curved roof adorned with ornaments symbolizing the Sultanate, and two pawestren (women’s prayer spaces) that are not found in the other comparative mosques. In addition to its distinctive architectural form, Masjid Dongkelan also holds significant socio-historical functions, serving as a center of community resistance during the colonial period and as a space for religious activities, education, and cultural preservation. The existence of Masjid Pathok Negoro Dongkelan represents adaptive Javanese-Islamic architecture that responds to environmental conditions and social needs, while at the same time maintaining traditional identity and its close association with the authority of the Yogyakarta Sultanate.